2004
DOI: 10.1093/humrep/deh471
|View full text |Cite
|
Sign up to set email alerts
|

Profound LH suppression after GnRH antagonist administration is associated with a significantly higher ongoing pregnancy rate in IVF

Abstract: Profound suppression of LH on day 8 of stimulation is associated with a significantly higher chance of achieving an ongoing pregnancy. More studies are necessary to evaluate this phenomenon further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 34 publications
0
42
0
7
Order By: Relevance
“…The highest implantation rate and ongoing pregnancy rate was present in those patients with LH levels on day 8 of stimulation ≤0.5IU/l. 16 In another study by Howles C M et al, in women undergoing IVF treatment with a combination of CC and hMG, there were no pregnancies recorded if the urinary output of LH was elevated when measured two days prior to the day of hCG administration. 5 Moreover, Stanger and Yovitch, have reported that high concentrations of luteinising hormone in the few days before oocytes were collected from women for in vitro fertilisation were associated with impaired rates of fertilisation and conception.…”
mentioning
confidence: 97%
“…The highest implantation rate and ongoing pregnancy rate was present in those patients with LH levels on day 8 of stimulation ≤0.5IU/l. 16 In another study by Howles C M et al, in women undergoing IVF treatment with a combination of CC and hMG, there were no pregnancies recorded if the urinary output of LH was elevated when measured two days prior to the day of hCG administration. 5 Moreover, Stanger and Yovitch, have reported that high concentrations of luteinising hormone in the few days before oocytes were collected from women for in vitro fertilisation were associated with impaired rates of fertilisation and conception.…”
mentioning
confidence: 97%
“…An alternative to GnRH agonists, GnRH antagonists have been proposed to prevent premature LH surge [ 16 ]. These drugs do not produce fl are-up effect, reducing synchronous follicular pool recruitment.…”
Section: Ovulation Induction and Intrauterine Insemination (Iui)mentioning
confidence: 99%
“…As a consequence, the oocyte/follicle unit may undergo dramatic and potentially detrimental changes due to the hormonal environment. On the other hand, a significantly higher pregnancy rate was described in patients with profound LH suppression (≤0.5 IU/l) on day 8 of stimulation (prospective, n = 116, r-hFSH 200 IU fixed from cycle day 2 and daily 0.25 mg GnRH antagonist from day 6 of stimulation) [62]. Some clinical trials have been designed in order to investigate the efficacy of LH supplementation in different subsets of patients treated with GnRH antagonists (Table 2) [63][64][65].…”
Section: Importance Of Flexible Lh Administration During Ovarian Stimmentioning
confidence: 99%